Tolkien and Comparative Historical Linguistics - Francesco Dedè (RiCognizioni, 2022)
It is a well-known fact that J.R.R. Tolkien’s training as a philologist had a very strong impact on his work as a creator of languages. This paper aims to identify the influence of Tolkien’s academic background in the field of linguistic studies on the creation of his Elvish languages. Taking into account Tolkien’s earliest works on Qenya (the first of the Elvish languages to be conceived) and based on our knowledge of Tolkien’s readings in linguistics and philology, the paper analyses some peculiar uses by Tolkien in describing the language and traces them back to their likely sources. The aim of the paper is twofold: on the one side, it hopes to show that this kind of source criticism can lead us to a better understanding of Tolkien’s conception of his Elvish tongues. On the other side, the systematic comparison between Tolkien’s writings on his constructed languages and the scholarly sources that constituted his linguistic background may represent a step towards acknowledging Tolkien’s place in the history of linguistic thought.